Réponses

2014-10-08T16:07:33+02:00
(-25)+(-13)-(+15)-(-13)-(-16)+(+14) = -25 -13 - 15 + 13 + 16 + 14 
= - 53 + 43 = -10

[(7-11)x(-6)+(-9)]x(-2) = (7 x -6 + -11 x -6 + -9) x (-2)
= (-42 + 66 - 9) x (-2)
= 15 x -2 
= - 30

  • Utilisateur Brainly
2014-10-08T16:09:34+02:00
(- 25) + (- 13) - (+ 15) - (- 13) - (- 16) + (+ 14)
= - 25 - 13 - 15 + 13 + 16 + 14
= - 25 - 15 - 13 + 13 + 16 + 14
= - 40 - 0 + 30
= - 40 + 30
= 30 - 40
= - 10

[(7 - 11) x (- 6) + (- 9)] x (- 2)
= [(- 4) x (- 6) - 9] x (- 2)
= (24 - 9) x ( - 2)
= 15 x (- 2)
= - 30
N'oublie pas de voter pour la meilleure réponse ! =)